Technical viability of citrus irrigation at north and northwest of Paraná state, Brazil - Calheiros, Rinaldo de Oliveira; de Oliveira, Dalziza; Caramori, Paulo Henrique; Grossi, Mauro Eduardo Del (Pesquisa Agropecuaria Brasileira, 1992)
The regions North (Londrina) and Northwest (Paranavaí) of Paraná State, Brazil, were studied about the technical viability of citrus irrigation. For this purpose the method of comparison among regions with regard to aspects of climate and soil was used with the parameters of temperature, insolation, precipitation, soil water storage capacity and daily water balance. The selected «standard reference» was the farm Sete Lagoas, located in Mogi Guaçu, São Paulo State. The results proved the high potential of irrigation use in all the studied conditions.